2003
DOI: 10.1124/jpet.103.051987
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide 1 Receptor Agonist ZP10A Increases Insulin mRNA Expression and Prevents Diabetic Progression indb/dbMice

Abstract: We characterized the novel, rationally designed peptide glucagon-like peptide 1 (GLP-1) receptor agonist H-HGEGTFTSDL-SKQMEEEAVRLFIEWLKNGGPSSGAPPSK KKKKK-NH 2 (ZP10A). Receptor binding studies demonstrated that the affinity of ZP10A for the human GLP-1 receptor was 4-fold greater than the affinity of GLP-1 (7-36) amide. ZP10A demonstrated dose-dependent improvement of glucose tolerance with an ED 50 value of 0.02 nmol/kg i.p. in an oral glucose tolerance test (OGTT) in diabetic db/db mice. After 42 days of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 36 publications
2
59
0
Order By: Relevance
“…2). Lixisenatide (Sanofi, Paris, France) is a 44-amino-acid derivate of exenatide, where the proline at residue 39 of exenatide is omitted and the C terminus is extended with six additional lysine residues (Thorkildsen et al, 2003) (Fig. 2).…”
Section: A Optimized Glucagon-like Peptide 1 Monoagonistsmentioning
confidence: 99%
“…2). Lixisenatide (Sanofi, Paris, France) is a 44-amino-acid derivate of exenatide, where the proline at residue 39 of exenatide is omitted and the C terminus is extended with six additional lysine residues (Thorkildsen et al, 2003) (Fig. 2).…”
Section: A Optimized Glucagon-like Peptide 1 Monoagonistsmentioning
confidence: 99%
“…Within the sequence of lixisenatide, the proline residue at position 39 of exenatide is omitted, and C-terminally extended with six additional lysine residues (Thorkildsen et al, 2003). Ultimately, this results in a slightly enhanced pharmacokinetic profile compared to exenatide with an estimated half-life of nearly 4 hours in humans, which permits once daily injections immediately before a fixed-time meal for comparable glycemic control as exenatide twice daily.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…In addition, long-term studies concerning clear cardiovascular end-points are needed; there exist many GLP-1 effects on the heart that are either receptor dependent or -independent (Ban et Once daily, phase III (Lyxumia) (Gerich et al, 2010). For ZP10, a prolonged-release formulation exists (Thorkildsen et al, 2003) ; structure in Leger et al, 2004); it allows for covalent binding to endogenous serum albumin and is protected against DPP-4 degradation (Guivarch et al, 2004); its half-life is similar to that of circulating albumin, approximately 10 to 15 days (De León et al, 2006;Nauck and Meier, 2005;Sinclair and Drucker, 2005;Christensen and Knop, 2010): no longer in active clinical development CJC-1134 A similar conjugate of albumin as CJC-1131, albeit with exendin-4 (Baggio and Drucker, 2007;Baggio et al, 2008;Christensen and Knop, 2010). It is given once weekly, in phase II; the half-life of albumin is the basis of the half-life of the compound CJC-1134-PC Same molecule as CJC-1134 except that it originates from exendin-4(1-39) instead of GLP-1 (Baggio et al, 2008 ; half-life of 3-6 h; no new data LY2189265 Phase II (Bastyr et al, 2010;Glaesner et al, 2010) PEG-DAPD PEGylated b DAPD (dual acting peptide for diabetes) ϭ GLP-1/glucagon hybrid peptide containing a maleimide-polyethylene glycol polymer (Claus et al, 2007); no new data Semaglutide (NN9535)…”
Section: E General Commentsmentioning
confidence: 99%
“…a For this novel, rationally designed peptide (H-HGEGTFTSDLSKQMEEEAVRLFIEWLKNGGPSSGAPPSKKKKKK-NH 2 ), the binding affinity for the human GLP-1 receptor is 4-fold higher than that of GLP-1 (7-36) amide (Thorkildsen et al, 2003) and an antiapoptotic effect was demonstrated (Tews et al, 2008).…”
Section: Vrs-859mentioning
confidence: 99%